Knowledge and relationship of consultants as key in management consulting industry: the case of Portugal consulting sector - Lopes da Costa, R.; Pereira, L.; Dias, Á.; António, N.; Gonçalves, R. (International Journal of Services, Economics and Management, 2021)
In a volatility, uncertainty, complexity, and ambiguity (V.U.C.A.) world the consultancy industry plays a critical role in helping companies to continues change and transform their business model. The scientific literature of management consulting affirms that this industry is an extraordinary sector and a phenomenon in the business context, however, theres a lack of research in this area to deeply understand how the sector is able to continue attractive and sustainable. To approach the lack of studies in this emerging area, this article aims to understand the role of consultants as knowledge-providers and simultaneously to realise the relative importance of the type of relationships to be built. Semi-structured interviews and questionnaires were applied to management consultants and SME managers in Portugal. Results show that consultants should provide not only a strategic but also structural perspective in the development of their work, relationships that are created within projects, between projects, and those that are created before projects.